Recording Regional Dialects in Labrador Inuttitut (Research Note) - Bejar, Susana; Johns, Alana; Nochasak, Christine (Études Inuit Studies, 2024)
This paper reports on the Elder’s Stories Project, an initiative to document regional dialects of Labrador Inuttitut across Nunatsiavut. The goal of this project is twofold: to preserve linguistic and cultural knowledge, with a focus on regional variation, and to create accessible spoken language resources for intermediate and advanced learners. The Elder’s Stories Project will pair audio recordings with time-aligned transcriptions using ELAN software. This method results in archival resources which enable learners and researchers to access and search oral texts linked directly to audio. The paper documents how the Elder’s Stories Project led to a series of ELAN transcription training workshops which in turn is becoming a catalyst for an interest in learning transcription skills among language specialists in Nunatsiavut.